How good are we at selecting students that meet our mission? Outcomes of the 2011 and 2012 entering classes selected by a locally developed multiple mini interview. (2nd December 2018) - Terregino, Carol A.; Copeland, H. Liesel; Laumbach, Sonia Garcia; Mehan, Daniel; Dunleavy, Dana; Geiger, Thomas
Abstract: Background: Can a locally developed multiple mini interview (MMI) process lead to outcomes reflective of local values and mission? Methods: In 2017, the authors performed a retrospective analysis of the relationship of MMI with multiple-choice-based outcomes and non-multiple-choice-based outcomes, including clerkship competencies, OSCE, scholarship/service/leadership, academic honor society induction, peer and faculty humanism nominations, and overall performance at graduation for two entering classes with acceptance decisions based exclusively on a locally developed MMI. Results: There was no association between MMI and performance on multiple-choice-based examinations. For other outcomes, the effect size of MMI for OSCE was small and leadership/service and scholarship did not correlate with MMI score. For clerkship competencies, there was medium effect size for patient care, practice-based learning and improvement, interpersonal and communication skills, and cultural competence. Highest and lowest quartile MMI scorers were no different in academic honor society induction; however, top quartile MMI scorers received more humanism votes versus last quartile and were more likely rated outstanding or excellent graduates. Conclusions: Local development of MMI and of admissions processes with sole reliance on MMI for final acceptance decisions will not affect academic preparation/medical school performance in multiple-choice-based assessments but can lead to locally desired attributes in students.